2012
DOI: 10.1002/cmdc.201200333
|View full text |Cite
|
Sign up to set email alerts
|

Partial Inhibition of Aldose Reductase by Nitazoxanide and Its Molecular Basis

Abstract: A little is more than enough: Aldose reductase (AR) is a potential target in a wide range of diseases but its utility may be limited by the side effects caused by complete inhibition. Furthermore, known inhibitors of AR have suffered in clinical evaluation due to poor bioavailability. Here, the clinically used antiprotozoal drug nitazoxanide with proven bioavailability has been shown to partially inhibit AR, potentially circumventing the negatives effects of complete enzyme inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 14 publications
2
23
0
Order By: Relevance
“…The shape of the open substrate‐binding pocket in AKRs is defined by loop 2, loop 4, and the C‐terminal loop. To the best of our knowledge, the structures of hAR·NADP + with d ‐glyceraldehyde and glucose‐6‐phosphate represent the only examples of substrate bound ternary complexes of an AKR superfamily member . Although Zheng et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The shape of the open substrate‐binding pocket in AKRs is defined by loop 2, loop 4, and the C‐terminal loop. To the best of our knowledge, the structures of hAR·NADP + with d ‐glyceraldehyde and glucose‐6‐phosphate represent the only examples of substrate bound ternary complexes of an AKR superfamily member . Although Zheng et al .…”
Section: Resultsmentioning
confidence: 99%
“…The specific transfer of the 4‐pro‐ R hydride to the carbonyl carbon atom of the substrate is known to be highly conserved in this superfamily. However, despite extensive structural studies (69 inhibitor bound AKR1 structures in the PDB), it is intriguing that only two structures of a substrate bound ternary complex of an AKR superfamily member have been reported, namely, hAR bound to d ‐glyceraldehyde (PDB: http://www.rcsb.org/pdb/search/structidSearch.do?structureId=3V36) and to glucose‐6‐phosphate (PDB: http://www.rcsb.org/pdb/search/structidSearch.do?structureId=2ACQ) .…”
Section: Introductionmentioning
confidence: 99%
“…The X-ray structure of human AKR1B1 in complex with D-glyceraldehyde and the NADP cofactor (PDB code 3V36) [54], as well as the co-crystal structure of human AKR1B1 in complex with a nitrofuryl-oxadiazol inhibitor (PDB code 2IKH) [55], were downloaded from the Protein Data Bank [56]. Molecular docking calculations were performed with GOLD 5.1 (CCDC Software Ltd., Cambridge, UK) [57] using the piecewise linear potential (PLP) fitness function.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…The beneficial effect of ALR-inhibitors in preventing diabetic complications provides strong support to the hypothesis that ALR1 and ALR2 inhibition could be an effective strategy in the prevention or delay of diabetic cataract. However, several ALR inhibitor studies are inconsistent with observations found in experimental animals and also in clinical trials to assess efficacy against various diabetic complications 22,79,80 . Interestingly, our in silico docking analysis shows that vitamin K1 competitively binds in both ALR1 and ALR2 and this binding site overlaps ~50% of the NADPH binding site.…”
Section: Discussionmentioning
confidence: 97%